STRATEGI PEMASARAN PAKET WISATA PADA PT. CAHAYA TEDUNG ABADI HOLIDAY DENPASAR - Doddy Pramana, Putu; Oka Karini, Ni Made; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2017)
PT. Cahaya Tedung Abadi Holiday is a business that handles tour ticket sales, travel documents, tour guide services, hotel reservation and sales of tour packages. To anticipate the traveler visits that always fluctuated and competition with other travel agency, need to be design tour package marketing strategy. So PT. Cahaya Tedung Abadi Holiday can optimize the strength, opportunities, and minimize the weaknesses and threats. The goal is to find alternative are strategies and programs that can be implemented by PT. Cahaya Tedung Abadi Holiday in selling tour package. Data collection techniques using the method of observation, in-depth interviews, library research and documentation. Researchers used a key informant Mr. I Gusti Sudarsana, two employees and sales marketing products as an informant base. This research is a descriptive qualitative with Matrix SWOT approach and the marketing mix. Alternative strategies that can be implemented by PT. Cahaya Tedung Abadi Holiday are : (a) create and develop tourism products strategy by creating new innovative tourism products and a special interest tour packages, (b) market segmentation strategy development with opportunities to develop a broader market, (c) increased promotion strategy by advertising, brochures and collaboration with TV channel with tourism programs information, (d) improve the quality of products and services strategies by redesigning the tour packages program more interesting in order the tourists interested to buy tour packages, maintaining cleanliness and tidiness of the vehicle and driver guides during tours and reemphasize tourism products according to the company market share. The suggestion for the company to expand its market share in order to survive the competition of other travel agencies, companies should increase the workforce to be more rapid and responsive in accepting tour packages purchases and fixed preserve good relations with related companies such as the hotel, restaurant, overseas agent, transport and tourism destination managers.
Keywords: Marketing Strategy, Tour Packages